Immediate effects of perturbation treadmill training on gait and postural control in patients with Parkinson’s disease - Klamroth, Sarah; Steib, Simon; Gaßner, Heiko; Goßler, Julia; Winkler, Jürgen; Eskofier, Bjoern; Klucken, Jochen; Pfeifer, Klaus (Gait & posture, 2016)
The study investigates immediate adaptations of gait and balance to a single session of perturbed treadmill walking in patients with Parkinson’s disease. 39 Parkinson’s patients in stage 1-3.5 of the Hoehn and Yahr Scale were randomized into one of two groups, stratified by disease severity: The experimental group (n=19) walked on a treadmill prototype which constantly applied perturbation by small three-dimensional tilting movements of the walking surface. The control group (n=20) trained on the identical treadmill without perturbations. Patients walked on the treadmill for 20min. Primary outcome measure was overground walking speed. Secondary outcomes were postural sway during quiet standing and spatiotemporal gait parameters during treadmill walking. Outcomes were measured repeatedly throughout the training session and after 10min retention. The experimental group significantly increased overground walking speed after intervention compared to the control group (p=0.014; ES=+0.41). Gait variability during treadmill walking significantly decreased after walking with perturbation. Sway area increased with treadmill walking only in the control group (p=0.009; ES=+0.49). No other postural sway measures changed over time. Subgroup analyses revealed that in the experimental group patients with more pronounced motor impairment demonstrated larger increases in overground walking speed (p=0.016; ES=+0.40) and stance phase symmetry (p=0.011; ES=−0.42). In conclusion, a single session of perturbation treadmill training led to gait improvements, which were more pronounced compared to unperturbed treadmill walking. Effects on static postural sway were less pronounced.